Prolactin levels during short‐ and long‐term cross‐sex hormone treatment: an observational study in transgender persons. (25th August 2016) - Nota, N. M.; Dekker, M. J. H. J.; Klaver, M.; Wiepjes, C. M.; van Trotsenburg, M. A.; Heijboer, A. C.; den Heijer, M.
Summary: The cause of prolactin alterations in transgender persons is often assigned to oestrogens, but the precise cause and time course during different phases of cross‐sex hormone treatment (CHT) remain unclear. In this study, we prospectively examined prolactin levels in 55 female‐to‐males (FtMs) and 61 male‐to‐females (MtFs) during the first year of CHT. Because long‐term prolactin data were not available in this population, we studied these levels in a retrospective population of 25 FtMs and 38 MtFs who underwent gonadectomy. FtMs were treated with testosterone and MtFs with estradiol, with or without the anti‐androgen cyproterone acetate (CPA) (after gonadectomy CPA is cessated). During the first year of CHT, prolactin decreased with 25% (95CI: −33%, −12%) in FtMs and increased with 193% (95CI: 156%, 219%) in MtFs. Eighteen MtFs developed hyperprolactinemia (≥0.6 IU L −1 ). In the retrospective population, post‐gonadectomy levels in FtMs were lower than baseline levels (−39%; 95CI: −51%, −20%) while in MtFs post‐gonadectomy levels and baseline levels were comparable (−6%; 95CI: −24%, 15%). No hyperprolactinemia was found after gonadectomy. In conclusion, in FtMs, prolactin decreased consistently during CHT and in MtFs, prolactin increased during pre‐surgical CHT but normalised after gonadectomy. It is likely that CPA induces increasing prolactin levels in MtFs.